Responsabilidade tributária, atos corruptivos e o alargamento do artigo 135 do Código Tributário Nacional - Pereira, Luciano de Almeida (2019)
All scientific work requires the selection of an instrument that serves as an investigative method. In other words, the cognitive being finds himself involved in a question that takes his psyche and, in his eagerness to get answers to these elements, that is, to the questions that cause him anxiety, he starts to investigate such questions that agitate him. spirit. In this work, we make use of Logical-Semantic Constructivism as an investigative way, as it understands to be the most cohesive and adequate way to obtain, satisfactorily, answers to the questions we bring to the present feat. As the title of the investigation on screen denotes, the primary concern here is about tax liability, especially that contained in Article 135 of the Brazilian Tax Code, since it is based on practices that stem from the misuse of powers conferred by instruments capable of giving administrative investiture to the subject, as well as in the non-observance of the law made by the individuals shown in article 134 of the same diploma. Indeed, our scientific discomfort does not end there. There are, equally, issues pertaining to the corrupt acts that accompany the practices that cause the impositions of the prescriptive statement to emerge, so that, from now on, the responsibility ceases to be the legal entity and becomes the personal of those agents spelled in the lines above highlighted article of law. Immediately, then, a question of fundamental importance starts to permeate our mind: what is a corrupt act? To what extent do corruptive acts have tax implications and, also, what mechanisms can be used to prevent them? It urges to stress, first of all, that a corrupt act is one done on the basis of corruption. But, what is corruption? What kind of corruption do we refer to in this work? In this way, any conception that is made about a corrupt act does not have to depart from the concept referred to above